Defluorination of bicarbonate water by galvano- and electrocoagulations - Deremeshko, L.A.; Kucheruk, D.D.; Balakina, M.M.; Goncharuk, V.V. (Reports of the National Academy of Sciences of Ukraine, 2016)
The efficiency of the cleaning of fluoride-bicarbonate waters by galvano- and electrocoagulation methods on model solutions and natural water from an artesian well is studied. It is shown that the presence of bicarbonate ions in water impairs the defluorination by galvanocoagulation and has no effect on the removal of fluorides by electrocoagulation. The basic physical and chemical mechanisms of these processes are established, and, on this basis, their operating parameters are determined by reaching the regulated concentration of fluorides in drinking water.